In situ growth of lead-free halide perovskites into SiO2 sub-microcapsules toward water-stable photocatalytic CO2 reduction. Issue 15 (27th March 2023) - Liu, Jie; Wu, Ziho; Zhang, Feng; Zhao, Mengzhen; Li, Chao; Li, Jie; Wen, Bo; Wang, Feijiu
Abstract : Cs2 AgBiBr6 @SiO2 composites synthesized via an in situ growth strategy showed much better stability compared with Cs2 AgBiBr6 modified only using ligands. Abstract : Halide perovskites (HPs) are highly susceptible to heat, light, or moisture and are easily decomposed even in an ambient environment, which greatly hinders their practical applications. Herein, an in situ growth strategy is presented for implanting an inorganic lead-free HP, Cs2 AgBiBr6, into SiO2 sub-microcapsules to form a Cs2 AgBiBr6 @SiO2 yolk–shell composite. The SiO2 sub-microcapsule endows Cs2 AgBiBr6 with good thermal and light stability, as well as excellent corrosion resistance against polar solvents. Furthermore, when employed as a lead-free perovskite photocatalyst, the composite exhibits a higher visible-light-driven CO2 -to-CO rate (271.76 μmol g −1 h −1 ) and much better stability than Cs2 AgBiBr6 in water. The formation of a Cs2 AgBiBr6 /SiO2 heterostructure using an in situ growth method alleviates water binding on the perovskites, supported by density functional theory calculations, which is the key to an improvement in the stability of the composite. The in situ growth strategy developed here sheds light on the design and development of HP-based materials for applications involving polar solvents.